Stimulus-responsive, gelatin-containing supramolecular nanofibers as switchable 3D microenvironments for cells - Hayashi, Kentaro; Matsuda, Mami; Nakahata, Masaki; Takashima, Yoshinori; Tanaka, Motomu (Polymers, 2022)
Polymer- and/or protein-based nanofibers that promote stable cell adhesion have drawn increasing attention as well-defined models of the extracellular matrix. In this study, we fabricated two classes of stimulus-responsive fibers containing gelatin and supramolecular crosslinks to emulate the dynamic cellular microenvironment in vivo. Gelatin enabled cells to adhere without additional surface functionalization, while supramolecular crosslinks allowed for the reversible switching of the Young’s modulus through changes in the concentration of guest molecules in culture media. The first class of nanofibers was prepared by coupling the host-guest inclusion complex to gelatin before electrospinning (pre-conjugation), while the second class of nanofibers was fabricated by coupling gelatin to polyacrylamide functionalized with host or guest moieties, followed by conjugation in the electrospinning solution (post-conjugation). In situ AFM nano-indentation demonstrated the reversible switching of the Young’s modulus between 2-3 kPa and 0.2-0.3 kPa under physiological conditions by adding/removing soluble guest molecules. As the concentration of additives does not affect cell viability, the supramolecular fibers established in this study are a promising candidate for various biomedical applications, such as standardized three-dimensional culture matrices for somatic cells and the regulation of stem cell differentiation.